Pengaruh Pendidikan Kesehatan Menggunakan Audio Visual terhadap Perilaku Oral Hygine pada Murid di SD Negeri 7 Bukit Tunggal Palangka Raya - Vita Natalia; Rizki Muji Lestari; Evy Kasanova; Victorius Victorius (Jurnal Surya Medika (JSM), 2022)
Background: Oral hygiene is a common way to clem any oral hygiene attached to the surface of the teeth and gums. Oral hygiene at the optimal time, like after eating in the morning and before bed at night. Phenomena that occur in grade SD Negeri 7 Bukit Tunggal Raya are still many students who don’t understand good and right oral hygiene and lack awareness of oral hygiene. Research Purpose: Analyze the effect of health education on oral hygiene behavior in students in grades 7 Bukit Tunggal Palangka Raya public elementary school in 2019. Research Method: Design this research is pre-experimental with a "one group pre-test and post-test design". Technic sampling is total sampling and Wilcoxon statistic test with 43 respondents. Result: The result with the Wilcoxon statistic test is Sig. (2-tailed) 0.00 smaller the p-value of 0.05, so H1 accept, it means the effect of using audio visual with oral hygiene behavior to school children in SD Negeri 7 Bukit Tunggal Palangka Raya 2019. Conclusion: The researcher advises that teachers can motivate the child to oral hygiene washing hands correctly, and they can apply that in their school or their house.